The horror readers' advisory : the librarian's guide to vampires, killer tomatoes, and haunted houses - Spratford, Becky Siegel (ALA readers' advisory series., 2004)
It's a dark and scary world. Fans are rabid. Blood, guts, and gore are the norm. Welcome to the horror genre. Horror classics have been scaring people for years. Nowadays, who doesn't know about Stephen King, Anne Rice, and Dean Koontz? Profiled in a special section, the "Big Three" have turned horror into best-sellers. For all the horror fans that haunt your library, this is the must-have guide. Readers' advisors and reference librarians will appreciate the key tools provided to expand upon this genre, including listings of top books, authors, and award winners within eleven horror subgenres-like mummies, biomedical, monsters, and splatterpunk. Clear descriptions of characteristics within subgenres are provided throughout. To further help you engage new readers, expert horror mavens Spratford and Clausen draw a savvy connection between film and horror as a potent reminder that the scariest movies have been adapted from novels. Their classic and contemporary recommendations like Rebecca, The Shining, and Rosemary's Baby reinforce activities between readers' advisors and library programming and open up the (cellar) door for further patron involvement. Readers' advisors and reference librarians will also learn: The art of the readers' advisory interview for horror Strategies to develop, and tools to market, the horror collection Tactics for introducing non-horror readers to the genre Where to go for more details and resources Horror may be an acquired taste, but under the guidance of two passionate aficionados, any librarian can master the basics to add horror into readers' advisory services